Cosmopolitan arthropod zooplankton in the Ordovician seas - Vannier, J; Racheboeuf, P; Brussa, E; Williams, M; Rushton, A; Servais, T; Siveter, D (2003)
Evidence is presented here for a zooplanktonic component in Ordovician marine ecosystems, namely the caryocaridid arthropods, that add to other well-documented midwater organisms such as graptolites, cyclopygid and telephinid trilobites, orthoconic cephalopods and the microphytoplankton (e.g. acritarchs). Although the soft anatomy of caryocaridids is largely hypothetical, their carapace design and ultrastructure, and their phyllocarid-like abdominal morphology (flattened furcal rami, telescopic segments) indicate a swimming lifestyle in midwater niches. Both functional and ecological interpretations are supported by their palaeogeographical and facies distributions and by analogies with modern pelagic ostracods. Caryocaridids occur at numerous localities on the palaeo-plates of Laurentia, Baltica, Avalonia, Perunica, Gondwana and South China and are recurrent faunal components of graptolitic black shales (mainly Tremadoc to Llanvirn). Typical faunal associates are the didymograptid and isograptid graptolites, pelagic cyclopygid and deep-sea benthic atheloptic trilobites. Their depositional environments suggest that the caryocaridids and their pelagic associates (graptolites) most probably thrived in waters above the distal shelf margins, where upwelling-controlled primary productivity possibly reached its maximum. Their exact bathymetrical range within the water column cannot be inferred from fossil evidence. However, their feeding strategies may have led them to exploit food resources across the mesopelagic-epipelagic boundaries as do numerous midwater crustaceans in present-day ecosystems. Caryocaridids represent a significant step in the post-Cambrian colonisation of midwater niches by arthropods and in the construction of complex modern foodwebs. © 2003 Elsevier Science B.V. All rights reserved.